ANALYSIS OF THE BEHAVIOR OF THE STUDENTS OF THE ENLARGED GROUP OF SPECIALTIES AND DIRECTIONS 44.00.00 EDUCATION AND PEDAGOGICAL SCIENCES IN SITUATIONS CONCERNING FIRST AID MEASURES - J. Marenchuk (Вестник Северо-Кавказского федерального университета, 2022)
The study is devoted to the analysis of the behavior of future teachers of an enlarged group of specialties and areas of «Education and Pedagogical Sciences» in situations related to first aid to victims. The concept of «first aid» is indicated. Experimentally (questionnaire) revealed the level of knowledge, skills of students in the field offirst aid to victims. Gaps in the knowledge of the school curriculum are identified. It is planned to further develop this field of knowledge in an educational institution, by studying students the discipline that contributes to the firm assimilation offirst aid materials and increasing their competence.